(untitled) (CIPEEX, 2022)
THIS RESEARCH AIMS TO ANALYZE PHILANTHROPY IN HEALTH AND EDUCATION IN GOIS FROM UK NEWSPAPERS. AN UNKNOWN COLLECTION ABOUT THE HISTORY OF BRAZIL CAN BE FOUND IN OTHER COUNTRIES. SPECIFICALLY, MUCH OF THE WORK CARRIED OUT IN HEALTH AND EDUCATION IN THE BRAZILIAN MIDWEST, BY PROTESTANT MISSIONARIES. THE WORKS DEVELOPED IN GOIS BY THE EVANGELICAL UNION OF SOUTH AMERICA MISSION, CURRENTLY, LATIN LINK, CAN BE FOUND AT THE CENTER FOR THE STUDY OF WORLD CHRISTIANITY, AT EDINBURGH UNIVERSITY, SCOTLAND. HOWEVER, A RICH SOURCE OF INFORMATION ABOUT THE ACTIONS OF MISSIONARIES CAN BE FOUND IN NEWSPAPERS AND MAGAZINES, IN THE MISSIONARIES’ HOMELAND. IN SOME PLACES, A KIND OF DIARY WAS RECORDED, REPORTING THE IMPORTANT DATES RELATED TO THEIR LIVES, SUCH AS THE CELEBRATION OF BEING SENT TO THE WORK CAMP, MARRIAGE, AND DEATH. IN ADDITION, THERE ARE DATA ON FUNDRAISING TO SEND TO PHILANTHROPIC ACTIVITIES, SPECIFICALLY, FOR HEALTH AND EDUCATION AGENTS WORKING IN GOIS. OBJECTIVES: CARRY OUT A CASE STUDY IDENTIFYING WHICH DOCUMENTS AND NEWSPAPERS DEALT MORE SPECIFICALLY WITH PHILANTHROPY IN THE UNITED KINGDOM - ANÁPOLIS RELATIONSHIP; UNDERSTAND HOW THESE ACTIONS WERE CARRIED OUT; WHAT THE MOTIVATIONS GENERATED AND HOW THIS CONTRIBUTION LEVERAGED THE EXPANSION OF HEALTH CARE FOR THE SERTANEJOS; TO ENCOURAGE THE WRITING OF ARTICLES, BOOKS, MONOGRAPHS AND THESES ON THE ROLE OF THE INTERNATIONAL RELATIONSHIP IN TERMS OF DEVELOPMENT IN THE HEALTH AND EDUCATION; EXPAND THE DOCUMENTARY COLLECTION OF CEDHOC/AEE. METHOD. A QUALITATIVE APPROACH IS CARRIED OUT BASED ON THE COMPREHENSIVE WEBERIAN SOCIOLOGY THAT INTERPRETS THE ACTIONS OF SUBJECTS BASED ON THE VALUES THAT GUIDE THEM (WEBER, 2000, 2001). IN THIS WAY, THE SUBJECTIVITY OF A GROUP OF PEOPLE OR INDIVIDUALS CAN BE PERCEIVED IN THE OBJECTIVITY OF THEIR RELATIONSHIPS, ACTIONS, AND INSTITUTIONS CREATED BY THEM. ALL ARE BASED ON THE ASPIRATIONS, BELIEFS, AND VALUES OF THE SUBJECTS. PARTIAL RESULTS: OBTAINING RELEVANT DOCUMENTS FOR THE UNDERSTANDING OF INTERNATIONAL INTERACTIONS, UNITED KINGDOM-ANÁPOLIS-GO, BASED ON PHILANTHROPY AND THE PROMOTION OF HEALTH AND EDUCATION DEVELOPMENT IN THE BRAZILIAN MIDWEST IN THE 20TH CENTURY. CONCLUSIONS: THE UNDERSTANDING OF THE RELATIONSHIP BETWEEN THE PIONEERS OF MEDICINE AND EDUCATION IN GOIS WAS EXPANDED, WITH ANÁPOLIS AS THE EPICENTER OF THIS INTERNATIONAL EXCHANGE AND AS THE AGENT THAT ENCOURAGED THE SENDING OF RESOURCES FROM ABROAD FOR ACTIONS AND INTENTIONS IN THE MIDWEST (CARVALHO, 2021). THIS SET OF DOCUMENTS WILL BE ENABLED INTERFACES WITH OTHER STUDIES PERMEATED BY INTERNATIONAL EXCHANGE. AND IT IS HOPED THAT THESE STORIES WILL INSPIRE PEOPLE TO WORK IN REGIONS LACKING RESOURCES AND PROFESSIONALS WITH A MORE HUMAN AND BROADER VISION OF THE POTENTIAL THAT EXISTS IN CULTURAL AND INTERNATIONAL PARTNERSHIPS AND EXCHANGES.